2022
DOI: 10.1155/2022/3463472
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Profile, Antimicrobial Susceptibility Pattern, and Associated Factors among Dental Caries-Suspected Patients Attending the Ayder Comprehensive Specialized Hospital and Private Dental Clinic in Mekelle, Northern Ethiopia

Abstract: Background. Dental caries is a major public oral infectious disease globally due to its high prevalence and significant social impact. Many studies have been conducted on dental caries in Ethiopia; however, they fail to convey the antimicrobial resistance in the oral environment. Objective. This study was conducted to determine the antimicrobial susceptibility patterns and biofilm formation in the bacteria isolated from dental caries and its associated factors of dental caries in THE Ayder Comprehensive Specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Based on the results of the research that has been done, it can be concluded that the concentration of cocoa bean extract has an effect on the formation of clear zones on Streptococcus mutans bacteria. As in the research, Streptococcus mutans has antibacterial properties (Kiros et al, 2022), and cocoa bean extract as a natural material in inhibiting the growth of Streptococcus mutans (Sanchez-Capa et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of the research that has been done, it can be concluded that the concentration of cocoa bean extract has an effect on the formation of clear zones on Streptococcus mutans bacteria. As in the research, Streptococcus mutans has antibacterial properties (Kiros et al, 2022), and cocoa bean extract as a natural material in inhibiting the growth of Streptococcus mutans (Sanchez-Capa et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…8 Another study carried out in Ethiopia reported Streptococcus mutans as the predominant microorganism among dental decay patients. 9 Streptococcus mutans was observed as the main and threat colonizer of the dental surfaces and was reported as persecutor to tooth damage in serious conditions of dental decay. 10 In Korea, Streptococcus mutans, Streptococcus sobrinus, and Lactobacillus spp were reported as etiological agents of dental decay among children where the proportion of Streptococcus mutans and Streptococcus sobrinus were significantly correlated with the color of the dental plaque.…”
Section: Discussonmentioning
confidence: 99%
“…Ampicillin, tetracyclines, and metronidazole showed the highest resistance rates, while azithromycin and ciprofloxacin had the lowest [81,[85][86][87]91].…”
Section: Studies Reporting Antimicrobial Resistance In Dentistrymentioning
confidence: 99%
“…Recent studies have investigated the emergence of antimicrobial resistance in some of the major pathogenic species of the oral cavity, including Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Tannerella forsythia, Prevotella spp., Streptococcus spp., Staphylococcus aureus, and Candida spp. [87,91,93].…”
Section: Antimicrobial Resistance In Major Periodontal Pathogensmentioning
confidence: 99%